2020
DOI: 10.1371/journal.pone.0228716
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of the impact of school characteristics on changes in physical activity opportunities

Abstract: Background Even as many states adopt physical activity policies to promote physical activity and prevent childhood obesity, little is known about differences in policy implementation based on school characteristics. We studied association of school characteristics and changes in physical activity opportunities at the school level during the implementation of a statewide physical activity policy in the state of Georgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recent research based in Georgia found a similar result in which geographical location of schools acted as a predictor of PA opportunities inside school, highlighting the importance of supplementing withinschool policy and environmental interventions to improve health disparities. 28 Lastly, our research could guide interventions to promote PA among youths. In 2021, Georgia ranked 14th in the nation for childhood obesity among youth aged 10 to 17-yearolds.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent research based in Georgia found a similar result in which geographical location of schools acted as a predictor of PA opportunities inside school, highlighting the importance of supplementing withinschool policy and environmental interventions to improve health disparities. 28 Lastly, our research could guide interventions to promote PA among youths. In 2021, Georgia ranked 14th in the nation for childhood obesity among youth aged 10 to 17-yearolds.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research based in Georgia found a similar result in which geographical location of schools acted as a predictor of PA opportunities inside school, highlighting the importance of supplementing within-school policy and environmental interventions to improve health disparities. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation